Farmers’ behaviour in risky decision-making - Enström, Martin; Eriksson, Johan (2018)
Risk is highlighted as an increasingly present aspect of the agricultural business, and it is important for agricultural producers to manage risk effectively. The implementation of risk management strategies and the adoption of risk management tools are some of the most complex decisions for farmers to execute. For Swedish farmers the private crop insurance is one available risk management tool to mitigate production risks caused by unforeseen weather events. Farmers’ decision behaviour in situations that include risk and uncertainty is a reflection of their risk propensity and risk perception. To explain farmers’ adoption of risk management strategies it is important to understand their decision-making behaviour.